Marketing strategy of the brand United Colors of Benetton aiming at generation Z - Čížiková, Terézia (2023)
This diploma thesis focused on assessing the global marketing strategy of the brand United Colors of Benetton aiming at the generation Z. In the theoretical part, crucial terms were introduced, including brand and marketing of the fashion brands. A closer look was also taken at the marketing strategy and the communication strategy of the fashion brands. Gen Z was described in detail, together with the market analysis of the Czech Republic. The practical part starts with the introduction of the brand United Colors of Benetton. Then the research results are introduced, based on which the recommendations for United Colors of Benetton were prepared. At the end, all important findings are concluded.